1958
DOI: 10.1212/wnl.8.6.435
|View full text |Cite
|
Sign up to set email alerts
|

Focal seizures due to chronic localized encephalitis

Abstract: OCCASIONAL SPECIMENS of scarred, atrophic brain removed for the relief of focal cerebral seizures at the Montreal Neurological Institute have shown striking perivascular collections of round cells, particularly in less severely damaged areas of these specimens. In the past this perivascular cuffing has been attributed to the effect on the brain of recurring seizures, with recognition, however, that this was a rather unsatisfactory explanation since the great majority of surgical specimens removed from patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
146
0
4

Year Published

1960
1960
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(166 citation statements)
references
References 4 publications
6
146
0
4
Order By: Relevance
“…Second, the IFNGR may form a complex with the AMPA receptor subunit GluR1 in neurons, leading to increased excitability and vulnerability to glutamate excitotoxicity (Mizuno et al, 2008). It thus seems plausible that CTL-derived IFN- sensitizes inflamed brain regions to epileptic seizures, which represents the earliest and most prominent manifestation of RE (Rasmussen et al, 1958;Bien et al, 2005). Of note, our present findings offer a potential explanation for the disease-enhancing effects of IFN- in an exploratory trial for MS (Panitch et al, 1987), a disease with prominent dendritic pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the IFNGR may form a complex with the AMPA receptor subunit GluR1 in neurons, leading to increased excitability and vulnerability to glutamate excitotoxicity (Mizuno et al, 2008). It thus seems plausible that CTL-derived IFN- sensitizes inflamed brain regions to epileptic seizures, which represents the earliest and most prominent manifestation of RE (Rasmussen et al, 1958;Bien et al, 2005). Of note, our present findings offer a potential explanation for the disease-enhancing effects of IFN- in an exploratory trial for MS (Panitch et al, 1987), a disease with prominent dendritic pathology.…”
Section: Discussionmentioning
confidence: 99%
“…A viral etiology has already been suggested by Rasmussen [1] based on the constituents of the immune reaction in the brain, such as lymphocyte infiltration and microglial nodules, but no pathogenic viral agents have been observed in any study subject [7,8]. Circulating autoantibodies, such as GluR3 and munc-18 [9,10], have also been suggested, but follow-up studies confirmed that those antibodies also existed in other diseases.…”
Section: Introductionmentioning
confidence: 98%
“…Rasmussen encephalitis (RE) is a rare progressive encephalitis that results in intractable seizures, cognitive decline and hemiparesis [1]. The affected hemispheres of RE patients are typically unilateral.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intractable focal epilepsy in children associated with progressive hemiparesis and cognitive impairment due to chronic encephalitis was first reported by Rasmussen et al [1]. Most of these patients suffer from epilepsia partialis continua characterized by focal motor seizures (Khozhevnikov’s syndrome), and the epileptic process spreads to involve the whole of one hemisphere.…”
Section: Introductionmentioning
confidence: 99%